Upaya Peningkatan Mobilisasi Pada Pasien Post Operasi Fraktur Intertrochanter Femur - Agustin, Ary, Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB, Dewi Suryandari, S.Kep., Ns., M.Kep (2017)
Background: Traffic accident can cause fracture. One of the fractures that often occur is intertrochanter femur fracture. Problems that occur in patients with fracture of one of them is limited motion, causing defects in the limbs fractured. Disability fracture can be restored gradually through the practice of functional activity and exercise to position the leg abduction. Objective: To describe the efforts increased mobilitation in patients intertrochanter femur fracture. Method: To descriptive method with case study approach in the ICU from 14th to 16th of February 2017. Collecting data with medical records, observation, interview, physical examination, books and journals on intertrochanter fracture femur. Result: After the intervention 3x24 hour patient showed no effect of increased mobilization and action functional activity and positioning exercise leg abduction. Conclusion: Exercise functional activity and leg position effectively improve the mobilization abduction. Suggestion: Exercise functional activity and leg position can abduction as an input in independent nursing action to deal with mobilization.